2017
DOI: 10.1179/2046905515y.0000000061
|View full text |Cite
|
Sign up to set email alerts
|

Hand-washing practices amongst mothers of under-5 children in Port Harcourt, Nigeria

Abstract: Hand-washing practices by mothers in Port Harcourt are poor. Extensive education of the public is required to reduce the risks of childhood infections associated with lack of hand-washing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…This indicates that knowledge alone is not enough for practicing good handwashing, other factors may have an influence for example, it might be the matter of behavior, 40,41 changing the habit is difficult, [42][43][44] their negative attitude towards the tangible effect of proper handwashing practice to control and prevent various communicable diseases, 45 and income. 39,46,47 A high-income family may live a higher quality of life because they have access to hygeine products unless they exhibit forgetfulness and laziness towards handwashing practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that knowledge alone is not enough for practicing good handwashing, other factors may have an influence for example, it might be the matter of behavior, 40,41 changing the habit is difficult, [42][43][44] their negative attitude towards the tangible effect of proper handwashing practice to control and prevent various communicable diseases, 45 and income. 39,46,47 A high-income family may live a higher quality of life because they have access to hygeine products unless they exhibit forgetfulness and laziness towards handwashing practices.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Evidence has indicated that effective handwashing practices can reduce the burden of global infectious disease transmission, especially diarrheal diseases. 2,3,[9][10][11][12][13][14][15][16][17][18][19] Around 2.4 million deaths could be prevented annually by good hygiene practices, reliable sanitation, and drinking water. 20 In addition, hand washing can reduce the occurrence of diarrheal diseases by 14-40%, 10,21,22 and educating mothers about personal hygiene can lead to a 27% decrease in the risk of infectious disease.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study conducted in slums of Hyderabad, Andhra Pradesh, among 506 households, of 451 children aged 6–59 months, stated that improved knowledge of caregivers was associated with higher odds of better child hygienic practices [20]. Similarly, a health facility based cross-sectional study conducted in Port Harcourt among 154 mothers of under-five children found that self-reported hand washing with soap and water before feeding the child and after cleaning the child was significantly associated with higher mothers' level of education [21]. This might be primarily due to changes in traditional beliefs, attitude, and improved WaSH practices in them.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of konduga LGA of Borno State, Ambe et al in 2008 documented prevalent cord care practices such as application of hot fermentation 31.5%, use of rag and lantern 19.5%, use of Vaseline 9.3%, use of ash/ charcoal 9.3%, use of red sand 3.5% respectively. 7 Opara et al, in their study of cord care by mothers in Port Harcourtin 2012, reported the use of petroleum jelly 58%, hot balms 20.3% antibiotic ointments 11.6% and use of toothpaste 5.8% 8 . In a study on the determinants of cord care practices carried out in Benin, Abhulimhen-Iyoha et al, reported that 76.8% of mothers who participated in the study were aware of beneficial cord practices and yet used other substances.…”
Section: Introductionmentioning
confidence: 99%